Association between habitual physical activity and stroke a case study in the Philippine General Hospital (PGH) and Jose R. Reyes Memorial Medical Center (JRRMMC) - Chua, Myra L. (2000)
To determine the association between habitual physical activity, as measured by the Baecke Questionnaire, and stroke among patients in the Philippine General Hospital (PGH) and Jose Reyes Memorial Medical Center (JRRMMC) from September to December 1999.The wards and out-patient clinics of various department (Neurology, Ophthalmology, Orthopedics, and Surgery) in the participating hospitals.Cases were patients who survived first stroke which occurred between September 1, 1998 and December 10, 1999 identified through the patient's medical chart or self-report. For each case, 2 age (?5) and sex matched controls, were selected from the same hospital as the case. Controls were patients with the following conditions: glaucoma and cataract (Ophthalmology), fracture and elective orthopedic surgery (Orthopedics), and hernias, hemorrhoids, and hydrocoele (Surgery).Ascertainment of patients' disease was done through the patient's medical chart or the discharge logbooks. Information on habitual physical activity and other relevant exposures were recorded using a structured questionnaire.A significant association was seen between high level of physical activity and stroke among less educated patients living within Metro Manila and more educated patients living outside Metro Manila. The odds of stroke in patients with high level of physical activity was higher among less educated residents of Metro Manila and lower among more educated residents of areas outside Metro Manila.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Cerebrovascular disease; Exercise